Impacto del bienestar universitario en los programas de pregrado y posgrado en la Universidad Santo Tomás Seccional Bucaramanga, Colombia entre 2009-2014 (2017)
The present article is the result of a documentary research centered in the analysis of institutional sources, on the report that the academic pairs of the Ministry of Education in Colombia when they visited the University Santo Tomás between the years 2009-2014, with the purpose, Renew the accredited programs of High Quality and the Qualified Registry. The study seeks to analyze the impact of the welfare factor when the institution was visited, since quality standards in higher education within the framework of university management, involve and increasingly emphasize the role of university welfare in terms of inclusion, coverage, Retention, satisfaction and social policies within an educational anthropology: the welfare of the community. Following a methodology of qualitative character when studying documentary sources in fifteen undergraduate courses and twenty-eight graduate programs; Among other things, the strengths of the impact of Welfare with its Retention and Academic Sustainability program (PAAI); the investigation; The program Moves USTA, the Educational Circle of Prevention and Integral Promotion (CEPI) project; Scholarship plan, support to teachers and undergraduate students to advance specializations, praise the management of the Department of Welfare in relation to the Institutional Education Project and higher education policies The academic peer report shows suggestions that are transcribed in the study, but the impact of the welfare factor is higher as confirmed by the reading of the sources.